Islamic Corporate Social Responsibility (ICSR) di Jakarta Islamic Index (JII): Analisis Mediasi dan Moderasi - Alim Syariati (Jurnal Iqtisaduna, 2022)
Jakarta Islamic Index (JII) emerges as a unique index in the Indonesian capital market with emphasize on the islamic values of the issuers. Consequentially, this ideological movement gives rise to the need of Islamic corporate social responsibility. This article investigates the determinants of this construct by quantitative measurement of the panel data from 2016-2018 forming a mediation, and moderation analysis in the Smartpls software. The results indicate the significant result between the Islamic board and the ICSR, but not toward the profitability—as how it affects ICSR. The mediation result does not get support from the finding. The moderating analysis implies that the larger the firm size, the more reduced the role of the Islamic board upon affecting the ICSR.